Study of Deformations That Occur on Road Surfaces and Develop Measures to Prevent Them - o’g’li, Qo’ysinaliyev Nuriddin Zafarali; o’g’li, Surobov Geroyjon Maxkamboy (Research Parks Publishing LLC, 2023)
In this article, you can pay attention to the fact that today's road construction is growing rapidly. It is being repeated again and again that we should pay great attention to the road sector.